Comunicación comercial y boca-oído electrónico en sitios web corporativos: Un análisis desde la perspectiva del marketing de relaciones - Daniel Belanche Gracia; Luis V. Casaló Ari\~no; Miguel Guinalíu Blasco (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– Due to the continuous growing of information exchange in the Internet, commercial web sites have started to include online tools to allow consumer interaction in them. Thus, when visiting these commercial web sites, consumers may consider not only e-retailer information (marketing communication) but also purchase and use experiences shared by other consumers (electronic word-of-mouth). This study focuses on the role of information included in a commercial web site in the improvement of the relationship with customers and the promotion of the e-retailer's products through electronic word-of-mouth. The results of the structural equations model based on commercial web sites' users suggest that marketing communication and electronic word-of-mouth positively affect the levels of affective commitment, whereas trust can only be affected by the degree of marketing communication. Finally, trust influences on commitment, and this in turn would directly affects the level of electronic positive word-of-mouth.
Keywords: M15; M30; M31; 330; Electronic word-of-mouth; Marketing communication; Trust; Affective commitment; Internet